If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 5x + -34 = 68 + -8x Reorder the terms: -34 + 4x + 5x = 68 + -8x Combine like terms: 4x + 5x = 9x -34 + 9x = 68 + -8x Solving -34 + 9x = 68 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -34 + 9x + 8x = 68 + -8x + 8x Combine like terms: 9x + 8x = 17x -34 + 17x = 68 + -8x + 8x Combine like terms: -8x + 8x = 0 -34 + 17x = 68 + 0 -34 + 17x = 68 Add '34' to each side of the equation. -34 + 34 + 17x = 68 + 34 Combine like terms: -34 + 34 = 0 0 + 17x = 68 + 34 17x = 68 + 34 Combine like terms: 68 + 34 = 102 17x = 102 Divide each side by '17'. x = 6 Simplifying x = 6
| 3x^(-1/2)-8=0 | | (a*a)-5a+25+(b*b)+6b+36=0 | | -6=3(x-19) | | 4x+x-15+x-4=180 | | 6-2x=6x-10x-16 | | 5b+6b-9b+1=7 | | 2(1-2a)=7(a-6) | | 2(x-3)-3=3 | | 11=4(n-17)+15 | | 7-z=-3 | | 12x+24y=60 | | ((4y^4/3x^4y^7))^3 | | 4s-3s=15 | | 8a^4=9a^2 | | 1/2:1/2 | | (a*a)-5a+25+(b*b)+6b+61=0 | | 11x+-9x-3=-9 | | G(x)=f(x+3)+1 | | (4y^4/3x^4y^7)^3 | | 11x+-9r-3=-9 | | c+x^2+40x=0 | | 13+x=y-17 | | -20x+5y=15 | | -5(r+7)=88 | | 2=4-6q | | 8-h=9 | | http://media.apexlearning.com/Images/200712/03/1536e7c5-c59f-4ae2-b5f1-51bc0e2ea368.gif | | 2(5+2x)=18+3 | | 1/3-x/7=1/21 | | (a-5)*2+(b+6)*2=0 | | 7x^1=-343 | | 7x^1=-342 |